Antioxidant, Anti-Tyrosinase, and Anti-Skin Pathogenic Bacterial Activities and Phytochemical Compositions of Corn Silk Extracts, and Stability of Corn Silk Facial Cream Product - Raenu Yucharoen; Pawalee Srisuksomwong; Jakaphun Julsrigival; Lapatrada Mungmai; Thida Kaewkod; Yingmanee Tragoolpua (MDPI AG, 2023)
Zea mays L. Poaceae stigma (corn silk, CS) is a byproduct of agricultural waste and is used as a traditional herb in many countries. CS is rich in chemical compounds known to benefit human health and is also a remedy for infectious diseases and has anti-proliferative effects on human cancer cell lines. In the present study, CS extract has been evaluated for its antioxidant, antibacterial, and anti-tyrosinase activities and its phytochemical composition. The higher total phenolic and flavonoid contents were found in the ethanolic extract of corn silk (CSA), at 28.27 ± 0.86 mg gallic acid equivalent/g extract and 4.71 ± 0.79 mg quercetin equivalent/g extract, respectively. Moreover, the antioxidant content of CSA was found at 5.22 ± 0.87 and 13.20 ± 0.42 mg gallic acid equivalent/g extract using DPPH and reducing power assays. Furthermore, the ethanolic extract of corn silk showed tyrosinase inhibition with an IC50 value of 12.45 µg/mL. The bacterial growth inhibition of CSA was tested using agar disc diffusion and broth dilution assays against Cutibacterium acnes and Staphylococcus epidermidis. It was found that CSA inhibited C. acnes and S. epidermidis with an inhibition zone of 11.7 ± 1.2 and 9.3 ± 0.6 mm, respectively. Moreover, the CSA showed MIC/MBC of 15.625 mg/mL against C. acnes. The following phytochemical compounds were detected in CSA: cardiac glycosides; n-hexadecanoic acid; hexadecanoic acid, ethyl ester; oleic acid; and 9,12-octadecadienoic acid, ethyl ester. After the corn silk cream product was formulated, the product demonstrated stability without phase separation. This research is beneficial for promoting effective ways to use agricultural waste while utilizing the antioxidant, anti-tyrosinase, and antibacterial activities of corn silk. Moreover, the use of technology and innovation to obtain high-value CS extract will benefit the development of commercial cosmetic products by providing safe, natural, and quality ingredients to the consumer.